Efeitos centrais de peptídeos derivados da hemoglobina: lvv-hemorfina-6 e lvv-hemorfina-7 - Cruz, Kellen Rosa da (2016)
LVV-hemorphin-7 (LVV-h7) and LVV-hemorphin-6 (LVV-h6) are bioactive peptides resulting from degradation of hemoglobin β-globin chain. LVV-h7 is a specific agonist of angiotensin IV receptor. This receptor belongs to the class of insulin-regulated aminopeptidases (IRAP), which also exerts oxytocinase activity. Herein, our aims were: i) to evaluate whether LVVs modify centrally-organized behavior and cardiovascular responses to stress and ii) to assess whether underlying mechanisms involve activation of oxytocin (OT) receptors, as result of reduction of IRAP proteolytic activity upon OT. Adult male Wistar rats (270-370g) received (ip) injections of LVV-h7 and LVV-h6 (153nmol/Kg), or vehicle (0.1ml). Different protocols were used: i) open field (OP) test for locomotor/exploratory activities; ii) elevated plus maze (EPM) for anxiety-like behavior; iii) forced swimming (FS) test for depression-like behavior and iv) air jet for cardiovascular reactivity to acute stress exposure. Diazepam (2mg/Kg) and imipramine (15mg/Kg) were used as positive control for EPM and FS tests, respectively. The antagonist of OT receptors, atosiban (1 e 0,1 mg/Kg), was used to determine the involvement of oxytocinergic paths. Both LVVs: i) increased the number of entries and the time spent in open arms of the maze, an indicative of anxiolysis; ii) reduced the immobility during FS test, an indicative of antidepressant effect; and iii) increased the exploratory activity, but locomotion episodes were significantly increased only by LVV-h7; while the specific OT antagonist, atosiban, did not revert the effect anxiolytic-like evoked by LVVs. It also changed the effects upon exploration evoked by LVV’s and the antidepressant-like effect promoted by LVV-h7. Besides, LVV-h6 and LVV-h7 did not change the cardiovascular reactivity and neuroendocrine responses to acute stress. We conclude that LVVs modulate behavior, display antidepressant and anxiolytic effects and do not change the cardiovascular reactivity to acute stress exposure. LVV-h7 behavioral effects are mediated in part by oxytocin receptors.